Genetic Algorithm-Based Optimization of Overcurrent Relay Coordination for Improved Protection of DFIG Operated Wind Farms - Rezaei N.; Uddin M.N.; Amin I.K.; Othman M.L.; Marsadek M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Asynchronous generators; Electric power system interconnection; Electric relays; Electric utilities; Genetic algorithms; Nonlinear programming; Overcurrent protection; Wind power; Conventional protections; Nonlinear characteristics; Nonlinear optimization methods; Overcurrent relay coordination; Overcurrent relays; Power system protection; Relay coordination; Wind farm; Electric power system protection